Mast Cells and Sensory Nerves Contribute to Neurogenic Inflammation and Pruritus in Chronic Skin Inflammation - Siiskonen, Hanna; Harvima, Ilkka (Frontiers in Cellular Neuroscience, 2019)
The intimate interaction between mast cells and sensory nerves can be illustrated by the wheal and surrounding flare in an urticarial reaction in human skin. This reaction is typically associated with an intense itch at the reaction site. Upon activation, cutaneous mast cells release powerful mediators, such as histamine, tryptase, cytokines and growth factors that can directly stimulate corresponding receptors on itch-mediating sensory nerves. These include, e.g., H1- and H4-receptors, protease-activated receptor-2, IL-31 receptor and the high-affinity receptor of nerve growth factor (TrkA). On the other hand, sensory nerves can release neuropeptides, including substance P and vasoactive intestinal peptide, that are able to stimulate mast cells to release mediators leading to potentiation of the reciprocal interaction, inflammation and itch. Even though mast cells are well recognized for their role in allergic skin whealing and urticaria, increasing evidence supports the reciprocal function between mast cells and sensory nerves in neurogenic inflammation in chronic skin diseases, such as psoriasis and atopic dermatitis, which are often characterized by distressing itch and exacerbated by psychological stress. Increased morphological contacts between mast cells and sensory nerves in the lesional skin in psoriasis and atopic dermatitis as well as experimental models in mice and rats support the essential role for mast cell-sensory nerve communication in consequent pruritus. Therefore, we summarize here the present literature pointing to a close association between mast cells and sensory nerves in pruritic skin diseases as well as review the essential supporting findings on pruritic models in mice and rats.